Inés and Pasionaria: The development of women before, during and after the Spanish Civil War in a novel by Almudena Grandes - Goñi Indurain, Maite (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The main aim of this paper is to analyze the representation of women who held the rearguard that allowed the clandestine struggle against Franco’s authoritarian regime that took place during almost the whole dictatorship in Inés y la alegría, a novel written by Almudena Grandes. For this purpose, in the first place, following a text by Judith Butler, we establish the importance of gender representation in order to create the perspective that we will follow for the novel’s analysis. Secondly, we took a tour of the role adopted by women in the first three decades of the twentieth century: from the social struggles that occur before the war and the first women’s voices that fought for equality until obtaining some rights partially due to the arrival of the Second Republic in 1931. In addition, we will also deal with the active involvement of women in the civil war both in the care of the rearguard and taking a rifle and fighting on the front line. Finally, we will highlight the importance of the work of women in the republican exile of 1939. After this, we focus on the analysis of the gender representation carried out by Almudena Grandes in Inés and la alegría, a novel in which the author brings to memory a very unknown episode of the Spanish postwar period, such as the incursion of the Aran Valley (Catalonia) and the subsequent formation of the clandestine struggle from the Spanish exile in France. We finish our work, stopping at the image that Almudena Grandes projects of one of the protagonists of her novel: «Pasionaria», whom the exile did not affect in the same way as to the militant women of her political party, for whom the secrecy supposed silence and subordination.